Engineering Design under Uncertainty and Health Prognostics - Hu, Chao.; Youn, Byeng D.; Wang, Pingfeng; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents state-of-the-art probabilistic methods for the reliability analysis and design of engineering products and processes. It seeks to facilitate practical application of probabilistic analysis and design by providing an authoritative, in-depth, and practical description of what probabilistic analysis and design is and how it can be implemented. The text is packed with many practical engineering examples (e.g., electric power transmission systems, aircraft power generating systems, and mechanical transmission systems) and exercise problems. It is an up-to-date, fully illustrated reference suitable for both undergraduate and graduate engineering students, researchers, and professional engineers who are interested in exploring the fundamentals, implementation, and applications of probabilistic analysis and design methods. .
Chapter 1. Basic Concepts of Reliability -- Chapter 2. Fundamentals of Probability Theory -- Chapter 3. Statistical Data Analysis -- Chapter 4. Fundamentals of Reliability Analysis -- Chapter 5. Reliability Analysis Techniques (Time-Independent).
Keywords: Security systems; Statistics .; Industrial organization; Security Science and Technology; Statistics in Engineering, Physics, Computer Science, Chemistry and Earth Sciences; Industrial Organization